Nilai Keislaman dalam Corak Motif Batik Pamekasan Madura Melalui Analisis Semiotika - Lulus Sugeng Triandika (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
The Madurese are described as very religious, many of their customs and cultural attributes represent Islam. Islam has influenced various aspects of Madurese culture. One of them is Madura batik which is quite famous. As a cultural heritage, Madura batik has historical and philosophical values.Pamekasan as a batik-producing area in Madura until now maintains its pattern of motifs from generation to generation. Although Batik Pamekasan has a characteristic use of plant and animal symbols. However, in detail, Islamic elements are seen more clearly in the pattern of Batik Pamekasan motifs than other coastal batik. So, it is interesting to study more deeply to know the influence of Islam in the pattern of Batik Pamekasan motifs. Although there have been many studies on batik, there is still little discussion of the value and meaning in its motifs. Especially currently there is still a lack of studies on the pattern of Batik Pamekasan motifs from the perspective of visual communication.This study uses a qualitative descriptive method, with data collection techniques through observation, literature study, and the results of interviews with sources. Charles Sanders Peirce's visual semiotic analysis is used to examine the object of research, namely the pattern of batik motifs.